Implementation of Pancasila Democratic Values in General Elections and Freedom of Expression in Indonesia - Melodi Rindu Kristianita; Fatma Ulfatun Najicha (Universitas Negeri Medan, 2022)
Pancasila democracy is a democracy that leads to the identity of the Indonesian nation. The journey of democracy in Indonesia still needs to go through a long process because it has not been fully implemented as it should. The implementation of democratic values in general elections and freedom of expression is one of the efforts that can be done to uphold democracy in the life of the state in the Unitary State of the Republic of Indonesia. This study aims to find out how important the implementation of the Pancasila values of Pancasila is in an effort to uphold democracy, especially in General Elections and Freedom of Opinion. The research method used is a qualitative method. This research is a literature study where all information and facts are sought from various sources such as books, articles, journals, and so on. Elections are one of the basic principles of implementing a democratic state which is contained in the fourth principle of Pancasila. Besides that, in a democracy every citizen is free to express his opinion in public as long as it does not conflict with the prevailing values. This article contributes as an additional reference that can help the community in conducting elections and expressing opinions. Based on the results of the discussion, it shows that the democratic value of Pancasila has a very important role in realizing the life of a democratic country, especially in general elections and freedom of expression in Indonesia.